Pengaruh Kompetensi Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening - Ismail, Melwan; Rahmisyari; Musafir (Melati Institute, 2024)
This study analyzes the effect of competence and performance allowances on employee performance, with motivation as an intervening variable, in the OPD of South Bolaang Mongondow Regency. The results are expected to provide recommendations for HR development policies to improve the quality of public services. These findings are important to support the efficiency and effectiveness of local government administration in serving the community. This quantitative study examines the effect of competence and performance allowances on employee performance, with motivation as an intervening variable, in the OPD of South Bolaang Mongondow Regency. Using a correlational survey model, the sample was taken using the Slovin Formula (305 respondents from 1,282 population, 5% error). Data analysis was conducted using the PLS method on SmartPLS 4, testing the causal relationship between variables to improve the quality of public services. This study tested seven hypotheses regarding the effect of competence and performance allowances on employee performance, with motivation as a mediating variable, in the OPD of South Bolaang Mongondow Regency. The results of the analysis show that competence and performance allowances have a positive and significant influence on employee performance, both directly and through motivation. This finding supports policies to improve human resources and employee welfare. This study concludes that competencies and performance allowances have a positive and significant effect on employee performance in the OPD of South Bolaang Mongondow Regency, both directly and through motivation. Competencies and performance allowances increase motivation, which in turn has a positive impact on employee performance, supporting the improvement of the quality of public services.